Inflation Crisis Management Strategies and the Performance of Hospitality Businesses in Osun State Nigeria (Journal of Management and Social Sciences, 2026)
Hospitality businesses in Nigeria were vulnerable to an inflation crisis following the removal of the fuel subsidy, which threatened their performance. The study examines how crisis management strategies affect the performance of the hospitality entities in Osun State, Nigeria. The four strategies examined in the study were human resource strategies (HRS), maintenance, marketing (MKT), and government support. Data were obtained from 206 hospitality business operators and employees using purposive sampling. Descriptive results show that maintenance-related strategies were the most employed, followed closely by human resources, marketing, and government support. Results from the regression indicate that human resource strategies positively impact all performance dimensions including, financial, employee and customer. Maintenance equally positively influence financial and employee but not customer performance. Marketing strategies positively impacts financial and customer performance, whereas government support impacts only the customer performance. Reinforcing HR, maintenance, and marketing measures is therefore central to achieving better performance in times of inflationary crisis.KeywordsCrisis, crisis management, inflation, hospitality sector, performance